Desterritorialização do Laticínio União no assentamento Barra da Onça em Poço Redondo/SE - Andrade, Mariana Barbosa (2017)
In the territory of the Sergipe High Outback, milk production is considered the main economic activity and its growth in the area is due to investments in public politics aimed at the genetic improvement of the herd, management practices appropriate to the semi-arid climate and as breeding strategy for family farmers. In Poço Redondo / Se, in the Barra da Onça settlement, the action of these politics made it possible to expand the mini plant formed by the Association of Small Rural Producers of Barra da Onça, which transformed it into União Milk Industry in 2001. Dairy production was centered on Pasteurized milk type C and derivatives. These products were sold in the commercial establishment, located in the city of Poço Redondo and in the capital Aracaju, surrounding municipalities and other States. Milk Industry União participated in the governmental social program Pró - Leite, PAA - Leite (Food Acquisition Program) and the National School Feeding Program (PNAE) - the main buyers of the small agroindustries certified as S.I.E. (State Inspection Service). Milk purchased by PAA-milk provided food to vulnerable families living in the municipalities of Poço Redondo, Canindé do São Francisco and Monte Alegre de Sergipe. The performance of these programs provided the expansion of agroindustries to meet Consumer needs of market throughout the State of Sergipe. However, the closure of the PAA-milk program accelerated the process of de-territorialization of the União Milk Industry and new territorialities were formed from it. Therefore, this research aims to analyze the process of territorialization, deterritorialization and (re) territorialization involved in the construction and closure of Laticínio União, as well as the new territorialities formed from it. A qualitative approach was adopted to understand the articulation of social networks in the functioning of social programs, as well as to understand the participation of actors, mediators and subjects in the direction of the milk production chain. Therefore, this research will demonstrate how this de-territorialization of União Milk Industry has been directly transformed the economy of the Barra da Onça settlement, provoking the emergence of new strategies of social reproduction.